Cells - Lewin, Benjamin;Ed. cassimeris, Lynne;Ed (Jones and Bartlett Publishers, 2007)
This textbook is designed for advanced undergraduate and early graduate courses in cell biology. It covers the structures, organization, growth, regulation, movements and interactions of cells, with emphasis on eukaryotic cells. Under the direction of Dr. Benjamin Lewin and three expert section editors, each chapter was prepared by top scientists who specialize in the given subject area, and all chapters have been carefully edited to maintain a consistent level throughout the text and to assure that all necessary topics are covered. Where they are known, the molecular bases for human diseases are discussed in each chapter.